2021
DOI: 10.1039/d1nj05108c
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale investigation of the effect of surface carbon coatings on the oxidation and mechanical properties of iron nanowires

Abstract: The understanding of the complex atomistic-scale mechanisms of the oxidation process of carbon (C) coated iron nanowires (Fe NW) and also the resulting modulation of mechanical properties is a highly challenging task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…34 ReaxFF has been successfully used for various systems, such as metallic Al, Ni, and Fe NWs to obtain insight into the oxidation of reactive complex materials and its responsible impact on degradation of mechanical deformation performance and predict related physical and chemical properties. 17,[26][27][28][29][30][31][32][33] Furthermore, these previous studies revealed that oxidized metallic NWs exhibit to have unique mechanical properties, which depends on several factors, such as the oxide shell layer thickness, the local structure of the oxide shell layer with the combined effect of the externally applied mechanical loads, determining the overall stress-strain behaviors in the NWs and the deformation mechanism and properties.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 ReaxFF has been successfully used for various systems, such as metallic Al, Ni, and Fe NWs to obtain insight into the oxidation of reactive complex materials and its responsible impact on degradation of mechanical deformation performance and predict related physical and chemical properties. 17,[26][27][28][29][30][31][32][33] Furthermore, these previous studies revealed that oxidized metallic NWs exhibit to have unique mechanical properties, which depends on several factors, such as the oxide shell layer thickness, the local structure of the oxide shell layer with the combined effect of the externally applied mechanical loads, determining the overall stress-strain behaviors in the NWs and the deformation mechanism and properties.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…The generated overall average stress vs strain is calculated from each atom using the virial theorem during the deformation process, which is corrected by the true volume of the NWs in order to obtain the engineering stress-strain curves in the [001]-oriented direction for each NW, as we used in previous MD simulations. 23,[26][27][28][29][30][31][32][33] The uniaxial tensile strain is applied until reaching at ∼28% elongation. Equations of motion are integrated with the velocity of the Verlet algorithm using a time step of 0.25 fs in all simulations.…”
Section: Simulation Detailsmentioning
confidence: 99%